Real School in the Virtual World Study on Online Learning in the Current Context of the Romanian Education System: Array - Stanciu, Filip; Popa, Doinita (Journal of Danubian Studies and Research, 2020)
The research report highlights concrete aspects, the real issue of online learning that teachers currently face, and the aspects they consider vulnerable for this form of education, which leads to imbalances in the teaching-learning-deepening-assessment. One important aspect is precisely the change in the mindset of teachers to overcome their common places and an openness to us, which is not within everyone's reach, and it is teachers who should continuously define and enrich their content by means of a flexible and open design adaptable to any requirements, while the student must develop their capacity to explore and analyze these contents in a collaborative manner, thus building a new teacher-pupil relationship. It is therefore important that in the next period, these aspects summarized in research, identified by teachers as practitioners, should be the starting point for the measures envisaged by the management bodies and those with authority in the field of education to address these discrepancies, solving system problems and improving education through the development of uniform educational strategies and policies based on studies and research results.